Catholic Sexual Ethics, Voices of Dissent, the Ecclesially Liminal and the Synodal Church: A Critical Theological Examination - Gigesh Thomas Meckal (Asian Horizons, 2025)
Some prominent theologians argue that to discern the sensus fidei it is sufficient to listen only to committed believers. However, this position is antithetical to Pope Francis’ conception of a synodal Church. The pope holds that it is important to listen to each member of the Church in order to discern the sensus fidei. This paper investigates Pope Francis’ vision, which includes those people who are on the existential periphery since their views on sexual ethics diverge from the official teachings of the Church. The lived experience of Christ’s disciples is pivotal to this discernment owing to the centrality of such experience to the sensus fidelium. This kind of discernment helps to integrate the believers who hold perspectives on sexual ethics that differ from the official teaching of the Church because of its attention to particular contexts of a problem, instead of providing a universal solution to ethical issues. Apart from the lived experience, due consideration of other sources of theology is inevitable for the accurate discernment of the movement of the Spirit in the faithful.